PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DENGAN KOMITMEN AFEKTIF SEBAGAI VARIABEL MEDIASI - Pradnyani, Luh Deni; Surya Putra, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023DO - 10.24843/EEB.2023.v12.i03.p06, 2023)
The purpose of this study was to analyze the influence of organizational culture on job satisfaction with affective commitment as a mediating variable which was carried out at the Klungkung Regency General Hospital. This study was conducted using a saturated sample of 75 people who are nurses. Data was collected by interview method and by distributing questionnaires. The data analysis technique used is structural equation (Structural Equation Modeling-SEM) based on variance or component based SEM, which is often called Partial Least Square (PLS). The results of this study indicate that organizational culture has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on affective commitment, affective commitment has a positive and significant effect on job satisfaction, and affective commitment is a variable mediating the influence of organizational culture on job satisfaction.